(untitled) (CIPEEX, 2025)
Objective: The study aims to compare agility in the 505 test Pre and Post an eight-week intervention of small-sided games in futsal athletes, without specific agility training. Materials and Methods: Thirty-one under-20 futsal athletes from IFPI Teresina Central Campus were evaluated, with an average age of 16 ± 1.63 years, body mass of 58.70 ± 10.37 Kg, and height of 1.72 ± 0.07 m, respectively; they were subjected to the 505 agility test before and after an 8-week intervention of small-sided games. Results: The results showed that there was an improvement in time (seconds), as the data consequently obtained better results in the Pre [3.09 seconds (2.88 – 3.20)] and in the Post [2.94 seconds (2.87 – 3.10)], demonstrating (Z = 2.460; p = 0.014), p>0.05. Conclusion: With eight weeks of reduced games, agility performance improves in futsal athletes.